(untitled) - Bolton, W. (Malaysia, 1998)
Control engineering provides a basic, yet comprehensive, introduction to the subject of control engineering for both mechanical and electrical engineering students. It is well written, easy to follow and contains many examples to reinforce understanding of the theory.
Keywords: Engineering,Mechanical and electrical